ANALISIS PENGARUH INFLASI, KURS, DAN SUKU BUNGA SERTIFIKAT BANK INDONESIA TERHADAP INDEKS HARGA SAHAM GABUNGAN MENGGUNAKAN REGRESI LINIER BERGANDA BAYES - Marta Widyastuti; Moch. Abdul Mukid; Yuciana Wilandari (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Jakarta Composite Index (JCI) is one of the stock price index emitted by Indonesia Stock Exchange (IDX). JCI is influenced by macro factors (external factors of a company) and micro factors (factors that come within the company). Some of the macro factors include inflation, exchange rate, and interest rate of Bank Indonesia Certificate. To obtain model of inflation, exchange rate, and interest rate of Bank Indonesia Certificate on JCI, Bayesian multiple linier regression can be used so that researcher is able to take into account prior information and apply it together with current data to obtain posterior estimation. From the data processing, it is known that interest rate of Bank Indonesia Certificate is not significantly influencing the model. Meanwhile, inflation and exchange rate are significantly influencing the model and both of them result 72,72% of R-Squared. Furthermore, the final model of Bayesian multiple linier regression proven to be very accurate because it has 4,951% of MAPE. Keywords: JCI, inflation, exchange rate, interest rate of Bank Indonesia Certificate, Bayesian multiple linier regression, prior, posterior, MAPE